MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN PENGEMBANGAN KARAKTER MELALUI THINK PAIR SQUARE SHARE (TPSS) DALAM LESSON STUDY - Muhfahroyin Muhfahroyin (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
The constructivist learning emphasizes that in learning a student constructs his knowledge with new knowledge which is obtained. The ability to construct knowledge relates to the ability of critical thinking, activity, and character. Therefore, constructivist learning as a device for the student to develop critical thinking activity, and character. The purposes of this research are to know the contribution of TPSS strategy toward the critical thinking, activity, character building. This research was implemented in the even semester academic year 2009/2010 in Biology Education Study Program FKIP UM Metro. Based on the research, the conclusion can be formulated that there was a contribution of TPSS strategy towards the learning activity, critical thinking, character building. The researcher suggests that teachers need to implement TPSS in biology learning, especially in Biology Education Study Program FKIP UM Metro.